Preparation method and application of copper-doped cerium oxide catalytic material
By preparing copper-doped cerium oxide catalytic material, the existing catalysts have poor thermal stability and low reaction activity have been solved, and the effect of efficient catalytic toluene is achieved, reducing the ignition temperature and improving the conversion rate.
Patent Information
- Application Number
- CN202411481624.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-05-02
AI Technical Summary
The existing catalysts have problems of poor thermal stability and low reaction activity when catalyzing toluene, making it difficult to effectively reduce the emission of toluene.
By preparing copper-doped cerium oxide catalytic materials, hydrothermal method and high-temperature calcination, the specific surface area and surface adsorbed oxygen content of the material are improved, thereby enhancing catalytic activity.
The efficiency of catalytic toluene is improved, the ignition temperature is reduced, the catalytic oxidation performance is enhanced, and the toluene conversion rate is reached at 371°C.
Smart Images

Figure CN119909693A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of toluene catalytic purification materials, and specifically relates to a preparation method and application of a copper-doped cerium oxide catalytic material. Background Art
[0002] As a typical emission from chemical production, transportation and interior decoration, volatile organic compounds (VOCs) are considered to be the "culprits" of haze, photochemical smog and various potentially harmful toxic substances, causing serious harm to the environment and human body. Toluene, as a typical volatile organic compound, is mainly produced in human activities. Most of it enters the environment directly to cause photochemical pollution, and a small part enters water bodies and soil through garbage and other channels to cause pollution. Exposure to toluene may seriously endanger human health, such as brain and nervous system disorders, short-term dizziness, headache or loss of consciousness; repeated exposure to high concentrations of toluene may cause permanent effects such as cognitive impairment, vision and hearing loss; long-term exposure to toluene by pregnant women can lead to delayed intellectual development of children and even spontaneous abortion. Toluene discharged into water bodies can cause the death of fish in the water and cause water pollution. In addition, it has the probability of producing photochemical ozone and secondary organic aerogels, which pollute the atmospheric environment. Therefore, it is of great significance to develop efficient and applicable methods to reduce toluene emissions.
[0003] At present, the main VOCs treatment technologies are: catalytic oxidation, thermal incineration, photocatalysis, biodegradation, plasma, membrane separation, etc. Among them, catalytic oxidation has the advantages of low reaction temperature, high efficiency, and less secondary pollution, and is considered to be the most promising volatile organic compound degradation technology. The key to catalytic oxidation technology lies in the development of high-efficiency catalysts. At present, catalysts are mainly divided into precious metal catalysts and non-precious metal catalysts. Precious metal catalysts represented by Pt, Pd, etc. have good low-temperature catalytic activity for aromatic compounds such as benzene and toluene. However, in view of the problems of expensive and poor anti-poisoning ability of precious metal catalysts, researchers have tried to use transition metals to replace precious metal catalysts. Among them, cerium-based catalysts are widely used in the field of atmospheric environmental pollution treatment because of their advantages such as more variable element valence states, higher catalytic oxidation activity, excellent oxygen storage / release capacity and low price. CeO 2 As a typical cerium-based catalyst, CeO has great application potential in catalysis due to its unique crystal structure. 2 The thermal stability is poor and low temperature is required for reactivity. Therefore, in order to further expand its application range, it is necessary to improve the disadvantages such as low reactivity and poor thermal stability through material modification. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a copper-doped cerium oxide catalytic material.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme: A method for preparing a copper-doped cerium oxide catalytic material, the method comprising the following steps: Step 1. Weigh the copper source and cerium source with a molar ratio of (0-0.008 mol): (0-0.008 mol) and place them in a beaker, and add deionized water to dissolve; Step 2, weigh 0.1-2g of silk fibroin and add it to the solution obtained in Step 1; Step 3, while stirring the solution obtained in Step 2, add a sodium hydroxide (NaOH) solution with a concentration of 1-5 mol / L, wherein the amount of the NaOH solution added is 1-5 mL, and continue stirring after the addition is completed, and the stirring time is 0.2-0.8 h; Step 4, transfer the solution obtained in Step 3 to a polytetrafluoroethylene liner, load it into a reaction kettle, and place it in an oven for hydrothermal aging, wherein the temperature of the hydrothermal aging is 20-120° C. and the time is 6-12 hours; Step 5, after the reaction is completed, take out the reactor and cool it, filter and wash the obtained solution, wash the precipitate with deionized water and ethanol respectively, and put the washed sample into an oven for drying; Step 6. The next day, the dried sample is placed in a muffle furnace and calcined at 200-600° C. for at least 4 hours, and then ground to obtain the copper-doped cerium oxide catalytic material.
[0006] Furthermore, the molar ratio of the cerium source to the copper source is (2-9):1.
[0007] Furthermore, the cerium source is cerium nitrate hexahydrate, and the copper source is copper nitrate trihydrate.
[0008] The copper-doped cerium oxide catalytic material prepared by the method.
[0009] The copper-doped cerium oxide catalytic material prepared by the method is used in catalyzing toluene.
[0010] Compared with the prior art, the present invention has the following beneficial effects: The copper-doped cerium oxide composite material prepared by the method provided by the present invention has an increased specific surface area and an increased surface adsorbed oxygen content, which promotes the formation of more oxygen vacancies and increases the mobility of lattice oxygen, thereby improving the catalytic activity of the cerium oxide catalytic material; the copper-doped cerium oxide composite material prepared by the method of the present invention effectively reduces the ignition temperature of toluene conversion, enhances the catalytic oxidation performance of the cerium oxide-based catalyst on toluene, and achieves a toluene conversion rate of 90% at 371°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 The SEM images of the copper-doped cerium oxide composite materials prepared in Examples 1 to 5 are shown in FIG. Figure 1 (a) Figure 1 (b) Figure 1 (c) SEM images at different magnifications; Figure 2 The copper-doped cerium oxide composite materials prepared in Examples 1 to 5 and the non-copper-doped cerium oxide catalytic material (CeO 2 -SF).
[0012] Figure 3 (a) Figure 3 (b) Figure 3 (c) and Figure 3 (d) are the copper-doped cerium oxide composite materials prepared in Examples 1 to 5 and the non-copper-doped cerium oxide catalytic material (CeO 2 -SF), full scan, O 1s orbital, Ce 3d orbital and Cu 2p orbital XPS spectra of the CuO catalytic material (CuO-SF) prepared in Comparative Example 2; FIG4 (a) and FIG4 (b) are respectively the copper-doped cerium oxide catalytic materials prepared in Examples 1 to 5 and the non-copper-doped cerium oxide catalytic material (CeO 2 -SF) nitrogen adsorption-desorption isotherm and pore size distribution curve; Figure 5 The copper-doped cerium oxide catalytic materials prepared in Examples 1 to 5 and the non-copper-doped cerium oxide catalytic materials (CeO 2 -SF), the catalytic performance diagram of the CuO catalytic material (CuO-SF) prepared in Comparative Example 2 for toluene. DETAILED DESCRIPTION
[0013] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0014] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0015] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention belongs. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention.
[0016] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to. Example 1
[0017] Weigh 0.0072 mol:0.0008 mol of cerium nitrate hexahydrate and copper nitrate trihydrate (copper-cerium molar ratio is 1:9) and place them in a beaker, record as 1Cu9Ce-SF, dissolve them in 55 mL of deionized water, weigh 1 g of silk fibroin and add it to the beaker, and add 3 mol·L -1 5 mL of NaOH solution was added, and stirring was continued for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, loaded into a reactor, and placed in an oven for hydrothermal aging at 120 °C for 6 h. After the reaction time was over, the reactor was taken out and cooled, the obtained solution was filtered and washed, and the precipitate was washed 3 times with deionized water and ethanol respectively. The washed sample was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5 °C·min -1 The temperature was raised to 550°C at a rate of 100 °C and maintained at a constant temperature for 4 h. The protein was removed by high-temperature calcination and the desired copper-doped cerium oxide catalytic material was obtained by grinding. Example 2
[0018] Weigh 0.0064 mol:0.0016 mol of cerium nitrate hexahydrate and copper nitrate trihydrate (copper-cerium molar ratio is 2:8) and place them in a beaker, record as 2Cu8Ce-SF, dissolve them in 55 mL of deionized water, weigh 1 g of silk fibroin and add it to the beaker, and add 3 mol·L -1 5 mL of NaOH solution was added, and stirring was continued for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, loaded into a reactor, and placed in an oven for hydrothermal aging at 120 °C for 6 h. After the reaction time was over, the reactor was taken out and cooled, the obtained solution was filtered and washed, and the precipitate was washed 3 times with deionized water and ethanol respectively. The washed sample was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5 °C·min -1 The temperature was raised to 550°C at a rate of 100 °C and maintained at a constant temperature for 4 h. The protein was removed by high-temperature calcination and the desired copper-doped cerium oxide catalytic material was obtained by grinding. Example 3
[0019] Weigh 0.0056mol:0.0024mol of cerium nitrate hexahydrate and copper nitrate trihydrate (copper-cerium molar ratio is 3:7) and place them in a beaker, record as 3Cu7Ce-SF, dissolve them in 55mL deionized water, weigh 2g of silk fibroin and add it to the beaker, and add 3mol·L iodine to the solution under stirring. -1 5 mL of NaOH solution was added, and stirring was continued for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, loaded into a reactor, and placed in an oven for hydrothermal aging at 120 °C for 6 h. After the reaction time was over, the reactor was taken out and cooled, the obtained solution was filtered and washed, and the precipitate was washed 3 times with deionized water and ethanol respectively. The washed sample was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5 °C·min -1 The temperature was raised to 550°C at a rate of 100 °C and maintained at a constant temperature for 4 h. The protein was removed by high-temperature calcination and the desired copper-doped cerium oxide catalytic material was obtained by grinding. Example 4
[0020] Weigh 0.007619 mol:0.000381 mol of cerium nitrate hexahydrate and copper nitrate trihydrate (copper-cerium molar ratio is 1.3:8.7) and place them in a beaker, record as 1.3Cu8.7Ce-SF, dissolve in 55 mL of deionized water, weigh 1 g of silk fibroin and add it to the beaker, and add 3 mol·L -1 5 mL of NaOH solution was added, and stirring was continued for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, loaded into a reactor, and placed in an oven for hydrothermal aging at 120°C for 6 h. After the reaction time was over, the reactor was taken out and cooled, the obtained solution was filtered and washed, and the precipitate was washed 3 times with deionized water and ethanol respectively. The washed sample was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5°C·min- 1 The temperature was raised to 550°C at a rate of 100 °C and maintained at a constant temperature for 4 h. The protein was removed by high-temperature calcination and the desired copper-doped cerium oxide catalytic material was obtained by grinding. Example 5
[0021] Weigh 0.006957mol:0.001043mol of cerium nitrate hexahydrate and copper nitrate trihydrate (copper-cerium molar ratio of 0.48:9.52) into a beaker, record as 0.48Cu9.52Ce-SF, dissolve in 55 mL of deionized water, weigh 1g of silk fibroin and add it to the beaker, and add 3mol·L -15 mL of NaOH solution was added, and stirring was continued for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, loaded into a reactor, and placed in an oven for hydrothermal aging at 120 °C for 6 h. After the reaction time was over, the reactor was taken out and cooled, and the obtained solution was filtered and washed, and washed with deionized water and ethanol for 3 times each. The washed sample was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5 °C·min -1 The temperature was raised to 550°C at a rate of 100 °C and maintained at a constant temperature for 4 h. The protein was removed by high-temperature calcination and the desired copper-doped cerium oxide catalytic material was obtained by grinding.
[0022] Weigh 0.008 mol of cerium nitrate hexahydrate into a beaker and record it as CeO 2 -SF was dissolved in 55 mL of deionized water, and 1 g of silk fibroin was weighed and added to a beaker. Under stirring, 3 mol·L -1 5 mL of NaOH solution was added, and stirring was continued for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, loaded into a reactor, and placed in an oven for hydrothermal aging at 120 °C for 6 h. After the reaction time was over, the reactor was taken out and cooled, the obtained solution was filtered and washed, and the precipitate was washed 3 times with deionized water and ethanol respectively. The washed sample was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5 °C·min -1 The temperature was raised to 550°C at a rate of 100 °C and kept at a constant temperature for 4 h. The protein was removed by high-temperature calcination and finally the cerium oxide catalytic material without copper doping was obtained by grinding.
[0023] Weigh 0.008 mol of copper nitrate trihydrate into a beaker, record it as CuO-SF, dissolve it in 55 mL of deionized water, weigh 1 g of silk fibroin into the beaker, and add 3 mol·L -1 5 mL of NaOH solution was added, and stirring was continued for 0.5 h. The solution was then transferred to a polytetrafluoroethylene liner, loaded into a reactor, and placed in an oven for hydrothermal aging at 120 °C for 6 h. After the reaction time was over, the reactor was taken out and cooled, the obtained solution was filtered and washed, and the precipitate was washed 3 times with deionized water and ethanol respectively. The washed sample was then placed in an oven for drying. The next day, the sample in the oven was placed in a muffle furnace and heated at 5 °C·min -1 The temperature was raised to 550°C at a rate of 100 °C and kept at a constant temperature for 4 h. The protein was removed by high-temperature calcination and the copper oxide catalytic material was finally obtained by grinding.
[0024] The scanning electron microscope (SEM) images of the copper-doped cerium oxide catalyst materials prepared in Examples 1 to 5 are as follows: Figure 1 As shown, Figure 1 (a) Figure 1 (b) Figure 1 (c) SEM images at different magnifications. Figure 1 It can be seen that under the induced synthesis of silk fibroin, the prepared copper-doped cerium oxide nanoparticles showed a certain agglomeration phenomenon, and the diameter of the large nanoparticles was about 8.5 nm.
[0025] The copper-doped cerium oxide catalytic materials prepared in Examples 1 to 5 and the non-copper-doped cerium oxide catalytic material (CeO 2 -SF) was characterized by X-ray powder diffraction (XRD), X-ray electron spectroscopy (XPS), and specific surface area analysis (BET). The characterization results are as follows: Figure 2 The copper-doped cerium oxide catalytic materials prepared in Examples 1 to 5 and the non-copper-doped cerium oxide catalytic materials (CeO 2 -SF). It can be seen from the figure that all catalytic materials have characteristic diffraction peaks of cerium oxide at 2θ values of about 28.55°, 33.08°, 47.48°, 56.33°, 59.09°, 69.40°, 76.70°, 79.07° and 88.41°, which are respectively attributed to the (111), (200), (220), (311), (222), (400), (331), (420) and (422) crystal planes of the face-centered cubic fluorite structure (JCPDS34-0394). With the increase of copper doping content, the intensity of the characteristic diffraction peak attributed to cerium oxide becomes lower and the diffraction peak becomes wider, indicating that the crystallinity of the material decreases. The XRD spectrum of the 1Cu9Ce-SF catalytic material prepared in Example 1 does not show any diffraction peaks that do not belong to cerium oxide, indicating that copper ions enter the cerium oxide lattice to form a copper-cerium solid solution. The highly dispersed copper species on the surface of cerium oxide can enhance the redox properties of the cerium oxide-based catalytic material and improve its catalytic performance.
[0026] Figure 3 (a) ~ Figure 3 (d) The copper-doped cerium oxide catalytic materials prepared in Examples 1 to 5 and the non-copper-doped cerium oxide catalytic materials prepared in Comparative Example 1 (CeO 2 -SF) full scan, O 1s orbital, Ce 3d orbital and Cu 2p orbital XPS spectra, revealing its elemental composition and chemical state. From the full scan spectrum, it can be seen that all catalysts contain C and O elements, which is due to the adsorption of polluted carbon in the surrounding air on the catalyst surface. The peaks of Ce and Cu elements appear in the copper-cerium composite catalyst, and the intensity of the copper peak gradually increases with the increase of the copper doping content. For the O 1s orbital spectrum, from Figure 3In (b), it can be seen that the fitted O 1s spectrum shows three characteristic peaks of different oxygen forms. The characteristic peaks at 529.41 eV~530.15 eV correspond to lattice oxygen (O latt ) peaks, and the characteristic peaks at 531.40 eV~532.63 eV correspond to the surface adsorbed oxygen (O ads ) peaks, and the characteristic peaks at 533.35 eV~533.92 eV correspond to the surface hydroxyl oxygen (O (OH) ) peak, the ratio of the characteristic peak area attributable to surface adsorbed oxygen and the peak area of O1s can be used to estimate the O removal in the catalyst. ads The content of α (O ads ), as shown in Table 1. Figure 3 (c) is the XPS spectrum of Ce 3d of the prepared catalytic material. u is used to mark the characteristic peak belonging to the Ce 3d3 / 2 spin orbit, and v is used to mark the characteristic peak belonging to the Ce 3d5 / 2 spin orbit. The peaks u′ (~886.01 eV) and v′ (~904.64 eV) are attributed to Ce. 3+ The characteristic peaks of , while u (~901.53 eV), v (~882.98 eV), u′′ (~908.14 eV), v′′ (~889.28 eV), u′′′ (~917.22 eV) and v′′′ (~898.81 eV) are attributed to Ce 4+ The characteristic peak is attributed to Ce by calculation. 3+ The ratio of the characteristic peak area of Ce to the peak area of Ce 3d can be used to estimate the Ce content in the catalyst. 3+ The content of α (Ce 3+ ), as shown in Table 1.
[0027] Figure 3 (d) is the XPS spectrum of Cu 2d of the prepared catalytic material. It can be seen from the figure that the characteristic peaks between 929.65 eV and 935.16 eV belong to the Cu 2p3 / 2 spin orbit, and the characteristic peaks between 949.01 eV and 955.07 eV belong to the Cu 2p1 / 2 spin orbit. Compared with the XPS spectrum of Cu 2d of CuO-SF, it can be clearly seen that the Cu 2d at around 940.99 eV and 960.65 eV 2+The shake-up peak of CuO-SF catalytic material was further fitted and analyzed. The peak at the lower binding energy (931.87 eV) was attributed to the Cu species (Cu-O) bound to the lattice oxygen, and the peak at the higher binding energy (933.87 eV) was attributed to the copper hydroxide species. The shake-up peak intensity in the 1Cu9Ce-SF catalytic material prepared in Example 1 was very weak, indicating that the copper species was highly dispersed on the surface of cerium oxide.
[0028] Table 1 lists the Ce, O, Cu contents and adsorbed oxygen content of each catalytic material prepared based on XPS spectra. 3+ The content.
[0029]
[0030] Table 1 FIG4 (a) and FIG4 (b) are respectively the copper-doped cerium oxide catalytic materials prepared in Examples 1 to 5 and the non-copper-doped cerium oxide catalytic material (CeO 2 -SF) nitrogen adsorption-desorption isotherm and pore size distribution curve. As shown in Figure 4 (a), according to the IUPAC isotherm classification, CeO 2 All curves of -SF and copper-doped cerium oxide catalytic materials belong to type IV isotherms with H3-type hysteresis loops, which have typical characteristics of microporous or mesoporous materials; the pore size distribution curve shown in Figure 4 (b) shows that the prepared catalytic materials contain a large number of mesopores, and the pore size distribution is mainly distributed between 3-10 nm. Table 2 lists the specific surface areas (S BET ), pore volume (V pore ) and average pore size. It can be seen from Table 2 that the copper-doped cerium oxide catalytic materials prepared in Examples 1 to 5 exhibit large specific surface area and pore volume. With the doping of metallic copper, the specific surface area of the copper-doped cerium oxide catalytic material decreases to a certain extent, and the trend of pore volume change is consistent with the trend of specific surface area. Generally speaking, a large specific surface area means that the catalyst can provide more reactive sites during the catalytic process, showing better catalytic oxidation performance.
[0031]
[0032] Table 2 The copper-doped cerium oxide catalytic materials prepared in Examples 1 to 5 and pure CeO 2 , CeO prepared in Comparative Example 1 2 The catalytic performance of toluene by CuO-SF and CuO-SF prepared in comparative example 2 is compared. The results are shown in Figure 5 .from Figure 5 It can be seen that the ignition temperature of 1Cu9Ce-SF catalyst is 270℃, and the ignition temperature of pure CeO 2 、CeO 2 The ignition temperature of the -SF catalyst is slightly higher, at 290 °C. When the toluene conversion rate is 50% (T50), pure CeO 2 CuO-SF and CuO-SF showed higher conversion temperatures, 348℃ and 360℃, respectively. In contrast, copper-doped cerium oxide catalytic materials showed lower conversion temperatures, and the T50 (289℃) of 1Cu9Ce-SF catalyst was reduced by about 60-70℃. The 1Cu9Ce-SF catalyst first reached a conversion rate of 90% at 371℃. The results of catalytic oxidation of toluene showed that the addition of copper to the cerium oxide catalyst was beneficial to improve its catalytic activity, reduce the starting temperature of toluene conversion, and enhance the catalytic oxidation performance of the cerium oxide-based catalyst for toluene.
[0033] It can be seen from the above test results that the copper-doped cerium oxide catalytic material prepared by the present invention has a large specific surface area and a high surface adsorbed oxygen content, and has many oxygen vacancies, which helps to improve the mobility of lattice oxygen. It shows high catalytic performance for toluene and can be used as a catalyst for the effective conversion of toluene.
[0034] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a copper-doped cerium oxide catalytic material, characterized in that: The method includes the following step: Step 1. Weigh the copper source and cerium source with a molar ratio of (0-0.008 mol): (0-0.008 mol) and place them in a beaker, and add deionized water to dissolve; Step 2, weigh 0.1-2g of silk fibroin and add it to the solution obtained in Step 1; Step 3, while stirring the solution obtained in Step 2, add a sodium hydroxide (NaOH) solution with a concentration of 1-5 mol / L, wherein the amount of the NaOH solution added is 1-5 mL, and continue stirring after the addition is completed, and the stirring time is 0.2-0.8 h; Step 4, transfer the solution obtained in Step 3 to a polytetrafluoroethylene liner, load it into a reaction kettle, and place it in an oven for hydrothermal aging, wherein the temperature of the hydrothermal aging is 20-120° C. and the time is 6-12 hours; Step 5, after the reaction is completed, take out the reactor and cool it, filter and wash the obtained solution, wash the precipitate with deionized water and ethanol respectively, and put the washed sample into an oven for drying; Step 6. The next day, the dried sample is placed in a muffle furnace and calcined at 200-600° C. for at least 4 hours, and then ground to obtain the copper-doped cerium oxide catalytic material.
2. The method for preparing a copper-doped cerium oxide catalytic material according to claim 1, characterized in that: The molar ratio of the cerium source to the copper source is 9:
1.
3. The method for preparing a copper-doped cerium oxide catalytic material according to claim 1, characterized in that: The cerium source is cerium nitrate hexahydrate, and the copper source is copper nitrate trihydrate.
4. The copper-doped cerium oxide catalytic material prepared by the method for preparing a copper-doped cerium oxide catalytic material according to any one of claims 1 to 3.
5. Use of the copper-doped cerium oxide catalytic material according to claim 4 in catalyzing toluene.
6. The use of the copper-doped cerium oxide catalytic material in catalyzing toluene according to claim 5, characterized in that: When catalyzing toluene, the ignition temperature is 250~300℃.